Glucose homeostasis in type 1 diabetic rats after acute physical activity - Moura, Leandro [UNESP]; Bertolini, Natalia [UNESP]; Ghezzi, Ana Carolina [UNESP]; Bertucci, Danilo [UNESP]; Bonfim, Mariana [UNESP]; Serafim, Thais Helena [UNESP]; Pereira, Aron [UNESP]; Garuffi, Marcelo [UNESP]; Mello, Maria Alice [UNESP]; Luciano, Eliete [UNESP] (My University, 2011)
Physical activity is considered an extremely effective therapy in cases of type 1 diabetes (DM-1), as it promotes glucose uptake independent of insulin action. However, there are few studies on the effect of a single session of exercise on glucose uptake in DM-1 (i.e., in the absence of insulin). Therefore, the purpose of this study was to assess the effect of a single exercise session on glucose homeostasis in DM-1 rats. For this purpose, 30 male rats were divided into three groups: sedentary control (SC), sedentary diabetic (SD), and exercise diabetic (ED). DM was induced by administration of alloxan and identified by the value of fasting glucose. The physical activity consisted of a single swimming session at the anaerobic threshold intensity for diabetic rats (3.5% body weight overload) for 30 min. The oral glucose tolerance test (OGTT) was performed immediately after the physical activity. The animals were sacrificed 48 hr after the OGTT, and samples were taken from the blood, liver, gastrocnemius, and mesenteric and subcutaneous adipose tissue. We observed that DM caused significant reduction in body weight. A single session of physical activity did not modify the response to the OGTT or glucose. However, it resulted in increased HDL cholesterol and hepatic glycogen content. These results suggest that, despite not having an effect on glucose homeostasis, acute physical activity performed at anaerobic threshold intensity leads to beneficial changes in the context of type 1 diabetes.
Keywords: Acute exercise; Diabetes; Glucose tolerance